2022
DOI: 10.3390/cells11030532
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-Induced Leucine Zipper Alleviates Lung Inflammation and Enhances Bacterial Clearance during Pneumococcal Pneumonia

Abstract: Pneumonia is a leading cause of morbidity and mortality. While inflammation is a host protective response that ensures bacterial clearance, a finely regulated response is necessary to prevent bystander tissue damage. Glucocorticoid (GC)-induced leucine zipper (GILZ) is a GC-induced protein with anti-inflammatory and proresolving bioactions, yet the therapeutical role of GILZ in infectious diseases remains unexplored. Herein, we investigate the role and effects of GILZ during acute lung injury (ALI) induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Therefore, the development of strategies to achieve increased levels of GILZ protein that do not involve treatments with GCs represents a way to restrain inflammation potentially applicable to various inflammatory diseases. The delivery of GILZ protein or GILZ-derived protein sequence has been tested in experimental models using cells and animal models [ 25 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. This approach was proven successful in inhibiting inflammation in experimental models, including ours and several other groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the development of strategies to achieve increased levels of GILZ protein that do not involve treatments with GCs represents a way to restrain inflammation potentially applicable to various inflammatory diseases. The delivery of GILZ protein or GILZ-derived protein sequence has been tested in experimental models using cells and animal models [ 25 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. This approach was proven successful in inhibiting inflammation in experimental models, including ours and several other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies indicate that GILZ over-expression, as well as in vivo delivery of the GILZ fusion protein, can achieve many of the anti-inflammatory effects of GCs, including inhibition of T-cell activation, proliferation and differentiation, and macrophage activation. To note, no apparent toxic effects have been ever observed in TAT–GILZ- or GILZ-peptide-treated mice [ 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies using GILZ knockout (KO) mice have shown that these mice exhibit decreased bacterial clearance and enhanced lung lesions when infected with S. pneumoniae. Conversely, the introduction of a cell-permeable transactivator of transcription (TAT)-GILZ fusion protein increased macrophage phagocytosis and reduced bacterial load in the lungs (Souza et al, 2022). TAT-GILZ treatment also enhanced macrophage influx with a regulatory phenotype in a model of E. coli-induced peritonitis in mice, accompanied by increased production of IL-10 and TGF-β levels, efferocytosis and bacterial clearance (Grossi et al, 2023).…”
Section: Gilz and Bacterial Infectionsmentioning
confidence: 99%
“…Additionally, TAT-GILZ, a fusion protein combining the cellpenetrating peptide TAT with GILZ, was found to induce the release of CCL2, facilitating monocyte/macrophage recruitment through the CCR2 receptor and resulting in accelerated resolution of E. coli-induced neutrophilic inflammation, increased peritoneal numbers of monocytes/macrophages, enhanced apoptosis/ efferocytosis counts, and improved bacterial clearance through phagocytosis (35). In the context of pneumococcal pneumonia, TAT-GILZ treatment reduced neutrophilic inflammation, enhanced macrophage efferocytosis, and improved bacterial clearance (34). Our findings in this study differ from our previous findings, which indicated enhanced phagocytosis and killing efficiency in GILZ KO macrophages (39).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Furthermore, studies have demonstrated that selective GILZ overexpression in macrophages improves outcomes in septic animals by limiting systemic inflammation while increasing bacterial clearance (32,33). The administration of a cell-permeable GILZ fusion protein (TAT-GILZ) facilitated the accelerated resolution of bacteria-induced pneumonia and peritonitis in mice, further underscoring the therapeutic potential of GILZ in modulating macrophagemediated inflammation (34,35).…”
Section: Introductionmentioning
confidence: 98%